Various Methods For Measuring Thermal Conductivity-A Review - Sekhu, Mr. Kulbir Singh; Singh, Mr. Parwinder (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The constant want for increasing heat transfer for a range of applications is one of the most complicated challenges faced by thermal engineers. With the innovation of technologies, heat transfer at higher rates and efficiency from small cross section areas or over low temperature difference are causing a rise in demands. As a consequence of the wide range of thermal properties there is no single measure method which can be used for all thermal Conductivity measurements. Consequently, over the past decades a wide variety of techniques for the enhancement of heat transfer has been suggested, where the most well-known and promising methods are briefly described in this paper. The study describes the steady state and transient methods for measuring thermal conductivity for different temperature ranges